Anthocyanic Vacuolar Inclusions: From Biosynthesis to Storage and Possible Applications - Buhrman, Kees; Aravena-Calvo, Javiera; Ross Zaulich, Clara; Hinz, Kasper; Laursen, Tomas (Frontiers in Chemistry, 2022)
The ability of plants to accumulate specific metabolites in concentrations beyond their solubility in both aqueous and lipid environments remains a key question in plant biology. Natural Deep Eutectic Solvents (NADES) are mixtures of natural compounds in specific molar ratios, which interact through hydrogen bonding. This results in a viscous liquid that can solubilize high amounts of natural products while maintaining a negligible vapor pressure to prevent release of volatile compounds. While all the components are presents in plant cells, identifying experimental evidence for the occurrence of NADES phases remains a challenging quest. Accumulation of anthocyanin flavonoids in highly concentrated inclusions have been speculated to involve NADES as an inert solvent. The inherent pigment properties of anthocyanins provide an ideal system for studying the formation of NADES in a cellular environment. In this mini-review we discuss the biosynthesis of modified anthocyanins that facilitate their organization in condensates, their transport and storage as a specific type of phase separated inclusions in the vacuole, and the presence of NADES constituents as a natural solution for storing high amounts of flavonoids and other natural products. Finally, we highlight how the knowledge gathered from studying the discussed processes could be used for specific applications within synthetic biology to utilize NADES derived compartments for the production of valuable compounds where the production is challenged by poor solubility, toxic intermediates or unstable and volatile products.